THE PHONOLOGICAL PROCESSES OF METATHESIS WORDS IN A CHILDS’ LANGUAGE ACQUISITION: A CASE STUDY OF A 3-YEAR-OLD CHILD - Nurul Intan Saputri; Albiansyah Albiansyah; Fahriany Fahriany (Lexeme : Journal of Linguistics and Applied Linguistics, 2021)
AbstractMetathesis is one of the unique phenomena among the children during their language acquisition phase. The aim of this study was to examine the phonological process of phenomena metathesis words that happen in a child’s language acquisition especially children with aged three half years. The participant of this research was a 3.5-year-old child. She is researcher’s daughter. The research method used in this research is qualitative method with a  case study design was employed in this study. The data were collected through observation, documentation, and daily notes or diary. The results of this research showed that the metathesis phenomena happen in that child was related to ten phonemes. It included pure metathesis in the same syllable phonemes, pure metathesis in the different syllable’s phonemes, metathesis followed by phonemes addition, and metathesis followed by phonemes omission. The study revealed some words containing metathesis that produced by the participant. Six pure metathesis words in the same syllable and six pure metathesis words in the different syllables then followed by addition phonemes involves in two words Keywords: Child, Language Acquisition, Metathesis, Phonemes, Phonological